Determinants of micro and small enterprises' (MSEs) growth in northwest Ethiopia. Issue 1 (2nd January 2022) - Andaregie, Adino; Worku, Aemro; Getachew, Belayneh; Fentahun, Yeshwas; Astatkie, Tessema
ABSTRACT: This article reports on a study that aimed to identify potential business constraints that hinder the economic development of micro and small enterprises (MSEs) in Ethiopia. Results of multiple linear regression and principal component analyses of data collected using stratified random sampling of 181 enterprise operators/managers showed that the age, gender, family size, and working experience of the operators, human capital, and limited access to market and productive resources were influential variables of enterprise growth. The findings of the study provide useful information on policy implications for the Government of Ethiopia and other similar African countries to enhance the growth of MSEs.